Regional Development Based on Leading Agricultural Commodities of Food Crop in Cianjur Regency, West Java Province, Indonesia - Gabrielle Khaledea Salimi; Sri Mulatsih; Andrea Emma Pravitasari (Jurnal Penelitian Pendidikan IPA, 2025)
In preparing the direction of the regional development plan, it is necessary to pay attention to determining the main focus of development. One of the strategies that can be used in Cianjur Regency is to develop areas based on leading agricultural commodities. This study aims to provide direction for regional development plan based on leading agricultural commodities of food crop in Cianjur Regency. The area that became the object of research consisted of 32 sub-districts. The data used in this study is harvest area of each comodities in 2019 - 2023. In determining the sub-district's leading commodities using Location Quotient, Differential Shift-Share analysis, and use Scalogram analysis to determining regional hierarchy. The results showed that paddy is the leading commodities on 15 sub-district’s or 47% of the total sub-districts in Cianjur, followed by cassava 28%, soybean 25%, corn and sweet potatoes 22%, and peanuts 19%.    7 (seven) sub-districts are included in hierarchy I, other 7 (seven) sub-districts are included in hierarchy II, and other 18 (eighteen) sub-districts are included in hierarchy III. Priority direction for regional development in Cianjur Regency is leading commodities in sub-districts with hierarchy I as the main regional development or in hierarchy II as the supporting regional development. The result of this study can also serve as a resource for contextual science education in the region, strengthening local scientific literacy and planning capacity